1998
DOI: 10.1046/j.1432-1327.1998.2530251.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and enzymatic characterization of a maltogenic amylase that hydrolyzes and transglycosylates acarbose

Abstract: A gene encoding a maltogenic amylase of Bacillus stearothermophilus ET1 was cloned and expressed in Escherichia coli. DNA sequence analysis indicated that the gene could encode a 69627-Da protein containing 590 amino acids. The predicted amino acid sequence of the enzyme shared 47Ϫ70% identity with the sequences of maltogenic amylase from Bacillus licheniformis, neopullulanase from B. stearothermophilus, and cyclodextrin hydrolase (CDase) I-5 from an alkalophilic Bacillus I-5 strain. In addition to starch, pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 8 publications
5
74
0
Order By: Relevance
“…2). A search with the BLAST program (43) revealed that the protein encoded by the ORF is homologous to neopullulanases (19,26), CDases (22,35), maltogenic amylase (6), and other amylolytic enzymes. It was suggested that the ORF encoded a kind of amylolytic enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…2). A search with the BLAST program (43) revealed that the protein encoded by the ORF is homologous to neopullulanases (19,26), CDases (22,35), maltogenic amylase (6), and other amylolytic enzymes. It was suggested that the ORF encoded a kind of amylolytic enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Although the Ca2 site is far from the active site, the presence or absence of calcium ions in the Ca2 site seems to affect the catalytic properties of the enzyme. The hydrolysis activities of MAases belonging to the type II group were increased by the addition of EDTA and decreased by calcium ions 28,31,42,43) although we still do not have a clear explanation. However, it seems obvious that the binding of calcium ions at the type II Ca2 site improves the catalytic activity of MAases (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…In isopanose, the ␣-1,6 linkage is located between the two glucose residues at the reducing end (25). The E. faecalis strain V583 has been shown to grow on panose (26), and several other bacteria were reported to utilize both panose and isopanose (27)(28)(29). We found that maltotetraose-positive E. faecalis JH2-2 can also grow on both maltotriose isomers (Fig.…”
Section: Substratementioning
confidence: 69%